Digital lighting and rendering - Birn, Jeremy ([S.l.] : New Riders, 2006)
Crafting a perfect rendering in 3D software means nailing all the details. And no matter what software you use, your success in creating realistic-looking illumination, shadows and textures depends on your professional lighting and rendering techniques. In this lavishly illustrated new edition, Pixar's Jeremy Birn shows you how to: Master Hollywood lighting techniques to produce professional results in any 3D application Convincingly composite 3D models into real-world environments Apply advanced rendering techniques using subsurface scattering, global illumination, caustics, occlusion, and high dynamic range images Design realistic materials and paint detailed texture maps Mimic real-life camera properties such as f-stops, exposure times, depth-of-field, and natural color temperatures for photorealistic renderings Render in multiple passes for greater efficiency and creative control Understand production pipelines at visual effects and animation studios Develop your lighting reel to get a job in the industry.